Direct addition and legacy effects of sulphur fertilisation on microbial soil organic matter mineralisation and priming effect - Yahaya Jebril Amanor; Eric Paterson; Nabla Kennedy; Aoife M. Duff; Patrick Forrestal; David P. Wall; Fiona Brennan (Soil Biology and Biochemistry, 2026)

Lessons learnt from the history and development of a national wildlife health surveillance scheme in England and Wales - J. P. Duff; A. Barlow; R. Delahay; J. P. Holmes; L. Martindale; G. Smith; J. A. Drewe (European Journal of Wildlife Research, 2026)
We provide a narrative history of the first government scheme to assess wildlife health in England and Wales. The Diseases of Wildlife Scheme started on a trial basis in 1998. It became established due to the significant national disease challenges from highly pathogenic avian influenza virus and West Nile virus. The development of the scheme reflected UK Government guidance on animal disease surveillance and also external published guidance, particularly from the European Wildlife Disease Association and the World Organisation for Animal Health. Within 11 years of starting this work it was sufficiently important to the government in England, that a national wildlife health strategy was produced. The England Wildlife Health Strategy provided further guidance incorporating the government’s expectations. One of the provisions of the Strategy was that the extensive range of wild species and diseases needed to be covered by a partnership of government and non-government organisations, with complementary specialisms. A further challenge was to forge an essential collaboration between the Animal Health and the Biodiversity departments of government. The history of the scheme reflects, at different levels, changes in wildlife health across Europe over the past 25 years, and the responses to deal with them. We reviewed the development and aims of wildlife health surveillance and use this to suggest a definition of national wildlife health surveillance. It is hoped that the lessons learnt may inform others in Europe and beyond, who are building surveillance schemes in this changing field.

Medically Tailored Grocery Delivery for Food Pantry Clients with Diabetes - Eliza Short; Ji Li; James P. Selig; Kelsey Bounds; Brett Rowland; Bonnie Faitak; Jazmin Lane; Rosana Solis-Garcia; Holly C. Felix; Krista Langston; Pearl A. McElfish; Juan Mejia-Otera; et al. (Journal of Nutrition Education and Behavior, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Manipulation of sward diversity is a more effective management strategy than addition of microbial inoculants in intensively managed grassland - Israel Ikoyi; Aoife M. Duff; John A. Finn; David P. Wall; Tanja Kostic; Eva Lucic-Mercy; Angela Sessitsch; Fiona Brennan (Plant and Soil, 2025)
Background and aims Diversifying grassland sward composition and application of microbial inoculants are potential alternative routes to facilitate enhanced nutrient acquisition by plants, but their relative effects have been rarely tested in grasslands. In a two-year field experiment, we investigated the impact of inoculants and sward types on forage yield, nutrient uptake, and the soil microbiome. Methods We implemented a fully factorial experiment with inoculants (eight levels; arbuscular mycorrhizal fungi (AMF), Paraburkholderia phytofirmans PsJN and Bacillus sp. P5 (P5), applied singly and in combination), and sward types (three levels: grass-only, grass and legume, mixture of grass, legume, and herb) as the two factors. Results In both years, there was a very strong effect of sward type, with the grass + legume and grass + legume + herb swards having much higher yields and nutrient uptake (N, P, K, S, Ca, Mg, Zn, Cu) than grass-only. Generally, there was no effect of the inoculants on yield and nutrient uptake, with limited exceptions involving AMF + P5. The best-performing microbial inoculant increased forage yield by 597 kg/ha/year, while switching from grass-only to one of the other sward types increased forage yield by 3932 kg/ha/year (grass + legume) and 4693 kg/ha/year (grass + legume + herb). The inoculants persisted in plots for > 1 year after application. Inoculants and sward type significantly affected the overall prokaryotic and fungal community structures. Conclusion Overall, under controlled field plot conditions, including legumes and herbs in a grass sward proved to be a far better farm-scale management strategy for increasing grassland forage yield and nutrient uptake than the application of microbial inoculants.

Economic impacts of a disease outbreak in Canada’s pork industry: Case of a price-taking, open country - Scott Biden; Alan P. Ker; Bruno Larue; Stephen Duff (Food Policy, 2024)

Forest reorganisation effects on fuel moisture content can exceed changes due to climate warming in wet temperate forests - Tegan P. Brown; Thomas J. Duff; Assaf Inbar; Patrick N. J. Lane; Gary J. Sheridan (Global Change Biology, 2024)
The distributions of vegetation and fire activity are changing rapidly in response to climate warming. In many regions, climate effects on dead fuel moisture content (FMC) are expected to increase future wildfire activity. However, forest FMC is largely driven by microclimate conditions, which are moderated from open weather by vegetation canopies. As shifts in vegetation increase under climate warming, the extent to which future fire activity will be driven by climate directly or associated vegetation shifts remains unresolved. Here, we present a study aimed at quantifying the relative magnitudes of (i) direct climate warming, and (ii) vegetation change, on FMC. Field sites to evaluate these effects were established in a natural laboratory of altered forest states to mature wet temperate forest in south‐eastern Australia. FMC was estimated using a process‐based model and 48 years of reconstructed climate data. Canopy effects on microclimate were captured by transferring inputs from climate to microclimate using models parameterised with field observations. To evaluate the relative magnitude of climate and vegetation effects, we calculated the maximum difference in mean annual FMC across annual climate replicates and compared this to FMC differences across reorganising forest sites. Our results show vegetation effects on FMC can exceed those related to expected climate change. Changes to forest structure and composition increased (+15.7%) and decreased (−12.3%) mean annual FMC, with a larger negative effect when forest cover was completely removed (−18.5%). In contrast, the largest climate effect on FMC was −6.6% across 48‐years of data. Our study demonstrates that the magnitude of vegetation effects on FMC can exceed expected climate change effects. Models of future fire activity that do not account for changing vegetation effects on microclimate are omitting a key biophysical control on FMC and therefore may not be accurately predicting future fire activity.

Grass finishing of Criollo cattle can provide an environmentally preferred and cost effective meat supply chain from United States drylands - José P. Castaño-Sánchez; C. Alan Rotz; Matthew M. McIntosh; Cindy Tolle; Craig A. Gifford; Glenn C. Duff; Sheri A. Spiegal (Agricultural Systems, 2023)

Production and characterisation of modularly deuterated UBE2D1–Ub conjugate by small angle neutron and X-ray scattering - Zuzanna Pietras; Anthony P. Duff; Vivian Morad; Kathleen Wood; Cy M. Jeffries; Maria Sunnerhagen (European Biophysics Journal, 2022)
This structural study exploits the possibility to use modular protein deuteration to facilitate the study of ubiquitin signalling, transfer, and modification. A protein conjugation reaction is used to combine protonated E2 enzyme with deuterated ubiquitin for small angle X-ray and neutron scattering with neutron contrast variation. The combined biomolecules stay as a monodisperse system during data collection in both protonated and deuterated buffers indicating long stability of the E2–Ub conjugate. With multiphase ab initio shape restoration and rigid body modelling, we reconstructed the shape of a E2–Ub-conjugated complex of UBE2D1 linked to ubiquitin via an isopeptide bond. Solution X-ray and neutron scattering data for this E2–Ub conjugate in the absence of E3 jointly indicate an ensemble of open and backbent states, with a preference for the latter in solution. The approach of combining protonated and labelled proteins can be used for solution studies to assess localization and movement of ubiquitin and could be widely applied to modular Ub systems in general.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Linking long-term soil phosphorus management to microbial communities involved in nitrogen reactions - R. M. O’Neill; A. M. Duff; F. P. Brennan; A. W. Gebremichael; N. T. Girkin; G. J. Lanigan; D. J. Krol; D. P. Wall; F. Renou-Wilson; C. Müller; K. G. Richards; C. Deveautour (Biology and Fertility of Soils, 2022)
The influence of soil phosphorous (P) content on the N-cycling communities and subsequent effects on N 2 O emissions remains unclear. Two laboratory incubation experiments were conducted on soils collected from a long-term (est. 1995) P-addition field trial sampled in summer 2018 and winter 2019. Incubations were treated with a typical field amendment rate of N as well as a C-amendment to stimulate microbial activity. Throughout both incubations, soil subsamples were collected prior to fertiliser amendment and then throughout the incubations, to quantify the abundance of bacteria (16S rRNA ), fungi (ITS) and Thaumarcheota (16S rRNA ) as well as functional guilds of genes involved in nitrification (bacterial and archaeal amoA, and comammox) and denitrification ( nirS , nirK , nosZ clade I and II) using quantitative PCR (qPCR). We also evaluated the correlations between each gene abundance and the associated N 2 O emissions depending on P-treatments. Our results show that long-term P-application influenced N-cycling genes abundance differently. Except for comammox, overall nitrifiers’ genes were most abundant in low P while the opposite trend was found for denitrifiers’ genes. C and N-amendments strongly influenced the abundance of most genes with changes observed as soon as 24 h after application. ITS was the only gene correlated to N 2 O emissions in the low P-soils while microbes were mostly correlated to emissions in high P, suggesting possible changes in the organisms involved in N 2 O production depending on soil P-content. This study highlights the importance of long-term P addition on shaping the microbial community function which in turn stimulates a direct impact on the subsequent N emissions.

Multiple primary malignancies associated with a germline SMARCB1 pathogenic variant - Judith A. Eelloo; Miriam J. Smith; Naomi L. Bowers; John Ealing; Paul Hulse; James P. Wylie; Patrick Shenjere; Noel W. Clarke; Calvin Soh; Richard W. Whitehouse; Mark Jones; Christopher Duff; et al. (Familial Cancer, 2019)

Imaging changes associated with cognitive abnormalities in Parkinson’s disease - Yuko Koshimori; Barbara Segura; Leigh Christopher; Nancy Lobaugh; Sarah Duff-Canning; Romina Mizrahi; Clement Hamani; Anthony E. Lang; Kelly Aminian; Sylvain Houle; Antonio P. Strafella (Brain Structure and Function, 2015)

Rainfall-Driven Amplification of Seasonal Acidification in Poorly Buffered Tropical Streams - Gaston E. Small; Marcelo Ardón; Alan P. Jackman; John H. Duff; Frank J. Triska; Alonso Ramírez; Marcía Snyder; Catherine M. Pringle (Ecosystems, 2012)

REX: Response Exploration for Neuroimaging Datasets - Eugene P. Duff; Ross Cunnington; Gary F. Egan (Neuroinformatics, 2007)

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

Inorganic nitrogen transformations in the bed of the Shingobee River, Minnesota: Integrating hydrologic and biological processes using sediment perfusion cores - Richard W. Sheibley; John H. Duff; Alan P. Jackman; Frank J. Triska (Limnology and Oceanography, 2003)
Inorganic N transformations were examined in streambed sediments from the Shingobee River using sediment perfusion cores. The experimental design simulated groundwater‐stream water mixing within sediment cores, which provided a well‐defined one‐dimensional representation of in situ hydrologic conditions. Two distinct hydrologic and chemical settings were preserved in the sediment cores: the lowermost sediments, perfused with groundwater, remained anaerobic during the incubations, whereas the uppermost sediments, perfused with oxic water pumped from the overlying water column, simulated stream water penetration into the bed. The maintenance of oxic and anoxic zones formed a biologically active aerobic‐anaerobic interface. Ammonium (NH + 4 ) dissolved in groundwater was transported conservatively through the lower core zone but was removed as it mixed with aerated recycle water. Concurrently, a small quantity of nitrate (NO − 3 ) equaling ~25% of the NH + 4 loss was produced in the upper sediments. The NH + 4 and NO − 3 profiles in the uppermost sediments resulted from coupled nitrification‐denitrification, because assimilation and sorption were negligible. We hypothesize that anaerobic microsites within the aerated upper sediments supported denitrification. Rates of nitrification and denitrification in the perfusion cores ranged 42–209 and 53–160 mg N m −2 day −1 , respectively. The use of modified perfusion cores permitted the identification and quantification of N transformations and verified process control by surface water exchange into the shallow hyporheic zone of the Shingobee River.

Regional Contamination in Lakes from the Noril'sk Region in Siberia, Russia - Jules M. Blais; Katharine E. Duff; Tamsin E. Laing; John P. Smol (Water, Air, & Soil Pollution, 1999)

A mini drivepoint sampler for measuring pore water solute concentrations in the hyporheic zone of sand‐bottom streams - John H. Duff; Fred Murphy; Chrsistopher C. Fuller; Frank J. Triska; Judson W. Harvey; Alan P. Jackman (Limnology and Oceanography, 1998)
A new method for collecting pore‐water samples in gravel streambeds is presented. We developed a mini drivepoint solution sampling (MINIPOINT) technique to collect pore‐water samples at 2.5‐cm vertical resolution. The sampler consisted of six small‐diameter stainless steel drivepoints arranged in a 10‐cm‐diameter circular array. In a simple procedure, the sampler was installed in the streambed to preset drivepoint depths of 2.5, 5.0, 7.5, 10.0, 12.5, and 15.0 cm. Sampler performance was evaluated in the Shingobee River, Minnesota, and Pinal Creek, Arizona, by measuring the vertical gradient of chloride concentration in pore water beneath the streambed that was established by the uninterrupted injection to the stream for 3 d. Pore‐water samples were withdrawn from all drivepoints simultaneously. In the first evaluation, the vertical chloride gradient was unchanged at withdrawal rates between 0.3 and 4.0 ml min − but was disturbed at higher rates. In the second evaluation, up to 70 ml of pore water was withdrawn from each drivepoint at a withdrawal rate of 2.5 ml min −1 without disturbing the vertical chloride gradient. Background concentrations of other solutes were also determined with MINIPOINT sampling. Steep vertical gradients were present for biologically reactive solutes such as DO, NH 4 + , NO 3 − , and dissolved organic C in the top 20 cm of the streambed. These detailed solute profiles in the hyporheic zone could not have been determined without a method for close interval vertical sampling that does not disturb natural logic mixing between stream water and groundwater.

Limnological characteristics of lakes located across arctic treeline in northern Russia - Katharine E. Duff; Tamsin E. Laing; John P. Smol; David R. S. Lean (Hydrobiologia, 1998)